Causality of fluid dynamics for high-energy nuclear collisions - Flörchinger, Stefan; Grossi, Eduardo (Arxiv, 2017)
Dissipative relativistic fluid dynamics is not always causal. We discuss the causality structure of high energy nuclear collision. When the fluid evolution equations are hyperbolic, one can bring them to a characteristic form describing the radial expansion of a fireball. This dynamics is causal if the characteristic velocities are smaller than the speed of light. We obtain a concrete inequality from this constraint and discuss how it can be violated for certain initial conditions. We argue that causality poses a bound to the applicability of relativistic fluid dynamics.